The ecology of a translocated population of a medium-sized marsupial in an urban vegetation remnant - Tomlinson, Sean; Smit, Anthony; Bateman, Bill (2021)
Although urbanisation can result in habitat loss, some species persist within urban vegetation remnants. Due to urban development, these species are often the targets of mitigation translocation; for example, the Quenda (Isoodon fusciventer, Marsupialia, Peramelidae), native to southwestern Australia. We assessed the foraging patterns and habitat preferences of a population of Quenda recently introduced by unknown agents to Kings Park, a large urban bushland remnant. Quenda foraged actively throughout our study area, but foraged most intensively in dense, low vegetation, with a significant preference for communities dominated by Banksia sessilis. This study joins other literature indicating that Quenda are able to persist in modified urban vegetation remnants despite the presence of predators, and human activity. Given the Quenda's clear adaptability to introduction into this urban remnant, we suggest that the greatest threat to continued persistence of urban populations of this species within remnants is likely to relate to difficulties in dispersing through surrounding urban areas. Nevertheless, the successful return of Quenda to a site that has traditionally been discounted from translocation programs suggests that other reserves in the region could also host introductions. Further research is required to determine whether Quenda can disperse through the surrounding suburbs, and whether it is possible to modify novel habitats to support Quenda populations within urban areas. Additionally, further research on facilitating dispersal through managing meta-populations in urban areas is required. Nevertheless, Quenda have successfully established at Kings Park, surrounded by dense urban areas. With ongoing management, urban remnants may be useful in Australia's protected area network.